Factors of weakness of the scientific level of students of the Department of Arabic language in the Kurdistan region of Iraq and how to promote it A field study on a sample of the teachers of the Department of Arabic Language and its students in the city - نزار خورشيد مامة; رشاد كمال مصطفى (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This field study tries to determine the most important factors of the weakness of the student level in the Arabic language in the Kurdistan region and to find successful solutions to these factors and reasons. The importance ofstudy lies in its reliance on field analysis and scientific and academic foundations in assessing the dimensions of the problem. The aim of this letter is to try to improve the reality of the Arabic language departments in the Kurdistan region of Iraq The purpose of this letter is to try to promote the reality of the Arabic language departments in the Kurdistan region of Iraq whenthe study in the schools of Kurdistan region became Kurdish after March uprising Hence, the problem of research and study lies in the weak level of students of Arabic language department in the Kurdistan region and the lack of mastery of most of the students of the basic language skills of Arabic language, especially after graduation. In the study, several questions raised on the factors and reasons that contributed in the low level of the student in order to find the appropriate solutions for this low level.